Analisis persebaran dan visualisasi penyakit Infeksi Saluran Pernapasan Akut (ISPA) dengan metode K-Means clustering pada Provinsi Jawa Tengah - Lazuardi, Febrian Bagaskara; Prillysca Chernovita , Hanna (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
Acute Respiratory Infection (ARI) is an infectious disease that often affects the upper and lower respiratory tract. This disease is one of the main causes of death in children under five, especially in areas with less favourable environmental conditions. This study aims to map the distribution of ARI in Central Java Province using the K-Means clustering method. Through data analysis that includes inputting, transforming, processing, and visualisation, this study successfully identified three clusters of areas with different levels of ARI distribution. Cluster 0 indicates areas with low risk, such as Demak and Semarang Regency, Cluster 1 indicates areas with medium risk, such as Klaten, Magelang Regency, Pati, while cluster 2 indicates areas with high risk, including Semarang City and Surakarta City. The results of this analysis are presented as a map using QGIS to spatially visualise the distribution of ARI across Central Java. Thus, local governments can design more effective and targeted ARI prevention and control strategies.